PENATAAN PEDAGANG KAKI LIMA: ANALISIS PASAR BISNIS PASAR MALAM DI LAPANGAN KODAM V BRAWIJAYA - Nova Retnowati (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2022)
Street vendors are one of Indonesia's assets that are of concern to the government related to local regulations regarding their arrangement. The purpose of the study was to determine the type of street vendor business market in the Kodam V Brawijaya Field, the daily turnover obtained by traders and to analyze the business market using SWOT. This analysis was carried out with a descriptive qualitative approach, in which the researcher systematically compiled the data obtained based on the results of interviews and group discussions. the results of the research and analysis that have been carried out, it can be concluded that in reality street vendors in the Field Kodam V Brawijaya grow and develop independently, so that the arrangement of street vendors needs local government support through regulatory strategies related to structuring and empowerment whose implementation needs to be stricter to minimize weaknesses by taking advantage of opportunities the resources that exist in the PKLi itself